Reaction of melon genotypes to Meloidogyne incognita and Meloidogyne javanica - Diniz, Guilherme Matos Martins; Candido, Willame Dos Santos; Soares, Renato Silva; Santos, Lucas Da Silva; Marín, Marcus Vinícius; Soares, Pedro Luiz Martins; Braz, Leila Trevisan (Escola de Agronomia/UFG, 2016)
ABSTRACT Melon is one of the most economically important crops cultivated in Brazil, especially in the Northeast region. However, as its cultivation increases, phytosanitary problems arise, including those caused by nematodes, which are most effectively controlled using resistant cultivars. This study aimed at assessing the reaction of muskmelon genotypes, in terms of resistance to Meloidogyne incognita and M. javanica infestation. The experiment was conducted under greenhouse conditions using a completely randomized design, in a 2 x 15 factorial scheme, with six replications. A total of 15 muskmelon genotypes were evaluated and the 'Santa Cruz Kada' tomato was used as a susceptible control. The total number of eggs and juvenile nematodes in the roots and the reproduction factor were used to assess the genotype reaction. None of the genotypes was resistant to M. incognita. Eight genotypes were classified as resistant to M. javanica and promising for use in melon breeding programs.

RESUMO O melão é uma das culturas de grande importância econômica no Brasil, especialmente para o Nordeste. Contudo, à medida que seu cultivo é intensificado, surgem problemas fitossanitários, dentre eles os causados por nematoides, cujo controle tem como medida mais efetiva o uso de cultivares resistentes. Objetivou-se avaliar a reação de genótipos de meloeiro quanto à hospedabilidade de Meloidogyne incognita e M. javanica. O ensaio foi conduzido em condições de casa-de-vegetação, utilizando-se delineamento inteiramente casualizado, em esquema fatorial 2 x 15, com seis repetições. Foram avaliados 15 genótipos de meloeiro, e o tomateiro 'Santa Cruz Kada' foi utilizado como padrão de suscetibilidade. Para avaliação da reação dos genótipos, utilizadram-se o número total de ovos e juvenis nas raízes e o fator de reprodução. Nenhum dos genótipos foi resistente a M. incognita. Oito genótipos foram classificados como resistentes a M. javanica e promissores para emprego em programas de melhoramento genético do meloeiro.
Reação de genótipos de meloeiro a Meloidogyne incognita e Meloidogyne javanica
Keywords: Cucumis melo L.; melhoramento de plantas; nematoides de galha; Cucumis melo L.; plant breeding; root-knot nematodes.